Improving Mutual Cooperation and Students' Cognitive Learning Outcomes using Problem Based Learning Assisted by Student Worksheets in Biology Learning - Meiliana Dwi Cahya; Aulya Nanda Prafitasari; Mohamad Abdul Somad; Ali Usman (PROGRAM STUDI PENDIDIKAN BIOLOGI FAKULTAS KEGURUAN DAN ILMU PENDIDIKAN UNIVERSITAS JEMBER, 2023)
Mutual cooperation is an important competency of the Pancasila student profile and can impact student learning outcomes. Applying PBL assisted by LKPD is expected to improve cooperation and students' cognitive learning outcomes (CLO). The study aimed to determine the increase in mutual cooperation and students’ CLO using PBL assisted by LKPD in biology learning. This type of research uses classroom action research. The research subjects were students at X1 Umbulsari Public High School, Jember, class X1, 2022/2023 academic year, with a total of 35 students. Classroom action research is implemented through the Plan, Do, and See stages. The study results show that the application of PBL assisted by LKPD can improve students' mutual cooperation and CLO. The increase in student cooperation is evidenced by an average value of 65 (cycle 1), 71 (cycle 2), and 87 (cycle 3). In contrast, students' CLO are evidenced by an average value of 57 (cycle 1), 84 (cycle 2), and 89 (cycle 3). The findings of this study can be a solution for educators to implement LKPD-assisted PBL as an alternative to improve cooperation and students' CLO.